A Systematic Review of How Circular Economy Models Are Operationalized in the Hospitality Industry - Warta Sumirat; Muhammad Fadhli Ramadhan; Erza Mutaqin (Integrasi Sains Media, 2025)
The transition to a Circular Economy (CE) is increasingly positioned as a strategic imperative for the hospitality industry to decouple growth from resource depletion. However, a significant disconnect remains between theoretical ambitions (